Performance Analysis of Microwave Photonic Spectral Filters based on Optical Microcombs - Yang Li; Yang Sun; Jiayang Wu; Guanghui Ren; Xingyuan Xu; Bill Corcoran; Sai Tak Chu; Brent E. Little; Roberto Morandotti; Arnan Mitchell; David J. Moss (Advanced Physics Research)
Abstract Microwave transversal filters, which are implemented based on the transversal filter structure in digital signal processing, offer a high reconfigurability for achieving a variety of signal processing functions without changing hardware. When implemented using microwave photonic (MWP) technologies, also known as MWP transversal filters, they provide competitive advantages over their electrical counterparts, such as large operation bandwidth, strong immunity to electromagnetic interference, and low loss when processing signals at high frequencies. Recent advances in high‐performance optical microcombs provide compact and powerful multi‐wavelength sources for MWP transversal filters that require a larger number of wavelength channels to achieve high performance, allowing for the demonstration of a diverse range of filter functions with improved performance and new features. Here, a comprehensive performance analysis for microcomb‐based MWP spectral filters based on the transversal filter approach is presented. First, the theoretical limitations are investigated in the filter spectral response induced by finite tap numbers. Next, the distortions are analyzed in the filter spectral response resulting from experimental error sources. Finally, the influence of input signal's bandwidth on the filtering errors is assessed. These results provide a valuable guide for the design and optimization of microcomb‐based MWP transversal filters for a variety of applications.